Durability of bituminous paving mixtures - Scholz, Todd V. (1995)
Bitumens are used as a binder in roadway pavements largely because they are relatively inexpensive and generally provide good adhesion and waterproofing characteristics. They are generally rather resistant to the detrimental effects of the environment and usually remain pliant for many years. In other words, bitumens are relatively inexpensive binders that generally provide good durability (or longevity of service) in pavement mixtures.